1974
DOI: 10.1099/00207713-24-3-358
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Preservation by Freeze-Drying of Pathogenic Bacteria of the Czechoslovak National Collection of Type Cultures

Abstract: On the basis of long-term experience with the preservation of the pathogenic bacteria of the Czechoslovak National Collection of Type Cultures, it is concluded that the suspending medium is a factor of primary importance in the preservation of these organisms in the freeze-dried state. The primary index of suspending medium effectiveness is the level of protection it affords against the adverse effects of low (subzero) temperatures, dehydration, long-term storage, and rehydration. A number of simple and compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In cattle with a weakened pulmonary defence, inhalation of the bacterium results in rapid colonization of the lungs and development of an economically important disease called shipping fever pneumonia (Rehmtulla and Thomson 1981). Lyophilization and freezing have been used for the preservation of this species as well as other members of the family Pasteurellaceae (Šourek 1974; Gibson and Khoury 1986; Aulet de Saab et al. 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In cattle with a weakened pulmonary defence, inhalation of the bacterium results in rapid colonization of the lungs and development of an economically important disease called shipping fever pneumonia (Rehmtulla and Thomson 1981). Lyophilization and freezing have been used for the preservation of this species as well as other members of the family Pasteurellaceae (Šourek 1974; Gibson and Khoury 1986; Aulet de Saab et al. 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Sourek (17) suggested that every bacterial strain of a given serological type had different viability characteristics. This conclusion was supported by the results of Gray and Lowe and by our own investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the ability of a bacteriological preservation medium to maintain stable cul- tures depends, to a large extent, on the methods used to recover and enumerate the cells after storage (5,15,17). Our inability to duplicate the results of Gray and Lowe, using nutrient with boric acid, may be related to our use of a pour plate, rather than a most-probable-number, technique for enumeration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain degeneration, which has been observed in a strain of Aspergillus versicolor producing versi-Colin, an antifungal antibiotic, is a fairly well established phenomenon. The maintenance of multiple cultures of an active strain has become a standard practice to meet the exigency (Raper & Alexander 1945;Buell & Weston 1947;Sourek 1974;Wellington & Williams 1977), although at times regeneration becomes an absolute need in the interest of a given research programme. Mutation techniques have been used successfully in the production of high, low or non-producer mutants or sometimes even producer mutants with an altered phenotype (Boronin 1970;Edwards et al 1974;Blumauerova et al 1976Blumauerova et al , 1978aLee & Ryu 1979;Simpson & Caten 1979;Takiguchi et al 1979…”
mentioning
confidence: 99%